Advances in Experimental Markets - Cason, Timothy; Noussair, Charles (Studies in Economic Theory, 2001)
Experimental methods are now a mainstream empirical methodology in economics. The papers in this volume represent some recent developments in research on experimental markets. The articles span a variety of topics related to experimental markets, including auctions, taxation, institutional differences, coordination in markets, and learning. Contributors to the volume include many of the most distinguished researchers in the area